ANTIMUTAGENIC POTENTIAL OF LIV52 BY AMES SALMONELLA/MAMMALIAN: MICROSOME MUTAGENICITY ASSAY - M, Radhakrishna; Mj, Hedge (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: Liv52, a nontoxic herbal preparation is reported to be clinically active in hepatotoxicity and a wide range of hepatic disorders. This study was undertaken to evaluate the mutagenic/antimutagenic potential of Liv52 using Salmonella mutagenicity test. Methods: Ames Salmonella/Mammalian - microsome mutagenicity test was used to evaluate the mutagenic or antimutagenic potential of Liv52. Salmonella typhimurium tester strains TA1537, TA1538, TA100, and TA102 were used for mutagenicity testing. The antimutagenicity study was carried out in tester strains TA1538 and TA100 against various standard mutagens with and without metabolic activation. Results: Liv52 did not show any mutagenic potential both with and without metabolic activation, whereas in TA1538 and TA 100 tester strains, Liv52 showed 48.4% and 47.2% of inhibition of his+ revertants induced by 4-nitro-O-phenylenediamine, respectively. Further with metabolic activation in TA1538, Liv52 showed 99.8%, 99.8%, and 100% inhibition of his+ revertants induced by 2-aminofluorene, 2-anthranine, and cigarette smoke condensate, respectively. In TA100 maximum of 100%, 100%, 97.7%, and 100% inhibition of his+ revertants induced by 2-aminofluorene, 2-anthranine, benzo(a)pyrene, and cigarette smoke condensate, respectively, were observed. A significant enhancement of inhibition of his+ revertants induced by all the above said mutagens were observed in preincubation modification method. Conclusion: Liv52 was found to be nonmutagenic in Salmonella assay, whereas manifested the antimutagenic potential both with and without metabolic activation. The enhanced antimutagenic activity of Liv52 on preincubation indicates that the antimutagenic factor(s) may be desmutagenic in nature. The exact mechanism by which Liv52 exerts antimutagenic potential is not known. The possibility of having diverse antimutagenic factors in Liv52 which act by different mechanisms are strongly indicated. Keywords: Liv52 syrup, Salmonella mutagenicity test, Ames test, Desmutagens.